Appropriateness of pharmacological treatment in older people with dementia - Eleonora Meloni; Davide Liborio Vetrano; Roberto Bernabei; Graziano Onder (Italian Journal of Medicine, 2015)
Dementia is associated with a number of comorbidities often observed in older people, including hypertension, cardiovascular disease, stroke and diabetes. Treating these comorbidities in older adults with dementia results challenging for many reasons. First, older adults with dementia are generally excluded from clinical trials, so application of clinical guidelines for treatment of chronic diseases in this population might lead to polypharmacy and adverse drugs effects. Second, memory, intellectual function, judgment and language are commonly impaired in patients with cognitive deficits, compromising the compliance to complex pharmacological regimens, increasing the risk of adverse drug reactions. Third, cognitive impairment is associated with limited life expectancy and therefore limits the efficacy of pharmacological treatments and questions the appropriateness of treatment. In the present study we examine most relevant concerns related to the treatment of comorbidities in demented patients, referring also to the existing criteria for inappropriate drugs in the elderly. The application of such instruments, along with the comprehensive geriatric assessment of the older adult with cognitive impairment, could result useful to reduce the burden of polypharmacy and inappropriate drug prescriptions.